Protection of Communal Intellectual Property Rights Through Geographical Indication System - Fenny Wulandari (Veteran Law Review, 2022)
This study aims to protect the original product/goods related to geographical conditions due to natural and/or human factors to be registered for protection through a Geographical Indication system that can be owned by the community communally. The research method used is normative juridical using secondary data. The law can be one of the tools to protect the regime of Geographical Indications by way of registration as regulated in Law Number 20 of 2016 concerning Marks and Geographical Indications. Article 53 reads: "Geographical Indications are protected after Geographical Indications are registered by the Minister". The main function of law is to protect the interests that exist in society. According to Roscou Pound, there are three interests that must be protected by law, namely: public interest, individual interest and interest of personality. Although most intellectual property rights protect individual property rights and individual interests, geographical indications are one that can be categorized as communal property rights.